Analysis Of Railroad Reactivation On Traffic In The Babat-Jombang Road - Zoya Aurora Putri Sulaiman; Sri Wiwoho Mudjanarko (Journal of World Conference (JWC), 2020)
The train is a mode of transportation that has many advantages. Already the supposed superiority used optimally ensure the movement of people and goods, This study uses a quantitative research. The analyzes were performed using the method of shock waves, based on Level of Service (Los) the degree of saturation in the biggest roadway there on days 1 and 2 towards Jombang-Babat at 8:00 to 9:00 pm at 0:26 into the category B where the value is less than the limit traffic density (0.26 <1). In the segment occurs queue as far as 624 meters long with 85 queues of vehicles takes time for 300 seconds from the start of the closing latch until the vehicle can run normally.